Drug Abused Victims Prevention through Sibolangit Rehabilitation Centre - Setyo Sumarno (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2016)
The study conducted to know the treatment used by Sibolangit Rehabilitation Center on preventing and handling drug abusers. The research found that the institution has been much helping the healing process of drug abuse victims.Thehealing can be seen from the physical condition of the client, healthy and increased in weight. Social changes after receiving service can be seen from having a lot of friends, sharing information and willing to follow the activities of the group.In mental and spiritual, the clients started to obey the rules in the institution, can take advantage of their spare time, mutually motivate among friends and have passion for a better life. Sibolangit Center treated many victims of drug abuse from all age groups, ranging from the youngest 14 years and the oldest 37 years old. In 2013, it rehabilitated 68 clients, in 2014 rehabilitated 65 clients, and in 2015 rehabilitated 60 clients. The success of the institution can not be separated from the support of various parties, such as administrative officers, sosial worker, counselor, doctors, victim’s friends, and families and communities to take part on making changes the clients. It is recommended that The Ministry of Social Affairs should informmore the public that Sibolangit Center is a place to help recover victims of drug abuse, so that is expectedto provide more information to individual, family or community to came to the center if needed.